HOMO LOQUENS OF THE NINETEENTH CENTURY: ELISÉE RECLUS AND HIS VISION OF SPAIN - MARINA Raevskaya (Ибероамериканские тетради, 2016)
The aim of the article is to define the contribution of Elisée Reclus, an outstanding French scientist and explorer of the 19th century, in shaping a new image of Spain which was based on the humanistic scientific ideas of the epoch. The paper gives a general overview of the ideas of Elisée Reclus formed under the influence of Karl Ritter, his German teacher. With this aim in view, the author of the article carries out an analysis of the ways of perception and interpretation of the geographic, historical, social and political reality in Spain in the second part of the 19th century in terms of geographic determinism. This approach proceeds from the assumption that the Man, as a constituent part of the natural order, is constantly affected by the environment. To get a better understanding of human habits and characteristics of a particular culture it is necessary to study its geographic conditions. The theoretical basis of the research determined the analytical and synthetic methods used in it. These methods made it possible to study the concrete materials (the authentic text by Elisée Reclus (1876)), to establish the correlation between scientific and philosophical principles of Elisée Reclus and his views on the geographic, eth-nographic, social and political reality in Spain at that time, to account for the conclusions he made on the basis of his ideas and observations in “Nouvelle Géographie Universelle” (“L´Espagne”).